External auditory canal exostoses in white water kayakers. Issue 2 (4th July 2008) - Cooper, A; Tong, R; Neil, R; Owens, D; Tomkinson, A
Abstract : Objective: In this study, the presence and severity of external auditory canal exostoses (EACE) in a group of white water kayakers related to the duration and intensity of kayaking and the number of ear infections reported were identified. Design: A community-based volunteer cross-sectional study was completed with 92 kayakers (69 men, 23 women; mean (SD) age 29.3 (8.72) years) and 65 control volunteers (37 men, 28 women; mean (SD) age 36.9 (14.9) years). After exclusions, 269 individual ears were examined (154 kayakers and 115 controls). Participants completed a questionnaire and underwent otoscopic examination. Main outcome measures were the presence and severity of EACE, the duration and frequency of kayaking and self-reported ear infections. Exclusion criteria included other cold-water exposure, known ear pathology or poor visualisation of the auditory canal. Results: The findings demonstrated that 69.5% of kayaker ears and 1.7% of the control group were found to have EACE. Severity of EACE was significantly associated with the duration (p<0.01) and frequency (p<0.05) of kayaking with 90.6% of kayakers that had participated for more than 10 years having evidence of EACE. A significant relationship also existed between the number of self-reported ear infections and the severity of EACE (p<0.01). Conclusion: There is a positive relationship between the duration and frequency of white water kayaking and the presence and severity of EACE and associated ear infections.